FAKTOR YANG MEMPENGARUHI INTERNET FINANCIAL REPORTING (IFR) PADA PERUSAHAAN MANUFAKTUR SUB SEKTOR FOOD AND BAVERAGE YANG TERDAFTAR DI BEI 2015-2019 - Arfian Candra Saputra; Endang Masitoh; Yuli Chomsatu Samrotun (Fakultas Ekonomi dan Bisnis, Universitas Muhammadiyah Cirebon, 2021)
This research was conducted in order to obtain empirical evidence about the effect of firm size, profitability, liquidity, and leverage on internet financial reporting (IFR). Samples taken in this study are manufacturing companies in the food and beverage sub-sector which are listed on the IDX 2015-2019. Sources of data used are secondary data, in processing this research data using multiple linear regression method. The sample in this study was obtained by purposive sampling method, in order to get 10 companies that meet the criteria and the data obtained in the study were 50 data. The results showed that firm size, profitability, and liquidity had an effect on internet financial reporting (IFR), while leverage had no effect on internet financial reporting (IFR). Keywords: IFR, Size, Profitability, Liquidity, Laverage.